INTRODUKSI TEKNOLOGI MESIN PENGEPRES DAN MESIN MIXERDALAM UPAYA PENINGKATAN PRODUKTIVITAS UKM MIE - Sunardi Sunardi; Soebiyanto Soebiyanto; Maria Endah Prasadja (LPPM UNS, 2016)
The purpose of this activity are: (1) improve the quality and productivity of UKM through the provision of machine presses for first partners and machine mixer for second partners; (2) help create tranquility, security and comfort in consuming wet noodle through noodle products that meet the quality requirements SNI 01-2987-1992; Specific target availability noodle products are hygienic and healthy appropriate quality requirements SNI 01-2987-1992.The results of activity are: (1) UKM Mie Pendowo has managed to increase its production through the provision of Machine Presses from 25 kg to 50 kg. It also increases the number of customers from 6 to 8 people. (2) UKM Mie OjoLali has managed to increase its production through the machine to make dough mixer become more effective and efficient. Supply of Machinery Mixer to increase the production of 150 kg / day to 175 kg / day. 3. BothUKM have been able to produce a wet noodle that meet the quality requirements specified in SNI 01-2987-1992.Kata kunci : Wet noodle, hygienic, healty